2018
DOI: 10.3390/e20040242
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation Analysis of Laminar Flows of Water-Based Nanofluids in Horizontal Minitubes under Constant Heat Flux Conditions

Abstract: During the last decade, second law analysis via entropy generation has become important in terms of entropy generation minimization (EGM), thermal engineering system design, irreversibility, and energy saving. In this study, heat transfer and entropy generation characteristics of flows of multi-walled carbon nanotube-based nanofluids were investigated in horizontal minitubes with outer and inner diameters of~1067 and~889 µm, respectively. Carbon nanotubes (CNTs) with outer diameter of 10-20 nm and length of 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Figure 9 demonstrates the comparison of the Fanning friction factor between the current results and the available experimental results from Karimzadehkhouei et al [ 66 ], Hussien et al [ 68 ], Jung et al [ 80 ], Lee and Mudawar [ 81 ], Ho et al [ 82 ], Hussien et al [ 83 ], and Peyghambarzadeh et al [ 84 ]. It is observed that our results agree favorably with the experimental data reported by Karimzadehkhouei et al [ 66 ], Lee and Mudawar [ 81 ], Ho et al [ 82 ], and Hussien et al [ 83 ], and our results are close to the available analytical data from Duan and Muzychka [ 76 ]. Most of the experimental data from Peyghambarzadeh et al [ 84 ] are close to the theoretical solution.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Figure 9 demonstrates the comparison of the Fanning friction factor between the current results and the available experimental results from Karimzadehkhouei et al [ 66 ], Hussien et al [ 68 ], Jung et al [ 80 ], Lee and Mudawar [ 81 ], Ho et al [ 82 ], Hussien et al [ 83 ], and Peyghambarzadeh et al [ 84 ]. It is observed that our results agree favorably with the experimental data reported by Karimzadehkhouei et al [ 66 ], Lee and Mudawar [ 81 ], Ho et al [ 82 ], and Hussien et al [ 83 ], and our results are close to the available analytical data from Duan and Muzychka [ 76 ]. Most of the experimental data from Peyghambarzadeh et al [ 84 ] are close to the theoretical solution.…”
Section: Resultsmentioning
confidence: 89%
“…Entropy generation minimization [ 52 , 53 ] and the principle of least action [ 54 , 55 , 56 ] are two important methods to study the performance optimization of a thermal system. Some efforts have been made to research into the entropy generation of different thermal systems [ 23 , 37 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. Khan et al [ 59 ] studied the performance of MCHS using an entropy generation minimization procedure, and proposed a general expression evaluating irreversibilities.…”
Section: Introductionmentioning
confidence: 99%
“…The larger exergy losses between evaporator inlet and outlet in the non-coated evaporator are due to i) higher wall superheats required for the onset of nucleate boiling, ii) non-uniform surface temperature due to lower number of active nucleation sites, iii) larger frictional pressure drop due to the presence of larger vapor bubbles [47], [48], [49]. Generated larger bubbles (Figure 5) on the non-coated evaporator results in larger bubble slip velocity and higher deformability, which all eventually increase the frictional pressure drop of the boiling flow inside the 2-m long evaporator [50].…”
Section: Exergy Analysis Second Lawmentioning
confidence: 99%
“…Moreover, entropy generation analysis results by Karimzadehkhouei, et al [21] show a significant increase in entropy generation while adding Al2O3 and TiO2 to the base fluid. The effect of slip boundary condition is not considered in their study as well.…”
Section: Introductionmentioning
confidence: 97%